Experimental and numerical analysis of image wavelength conversion with a Raman shifter - Manahan, Grace Gloria
We investigate the propagation dynamics through a nonlinear Raman-active medium of an image-carrying laser excitation beam and its wavelength conversion. A numerical model based on the finite difference (FD) method is used to solve the stimulated Raman scattering (SRS) wave equations. Different images at the laser excitation wavelength are simulated for down conversion to the Strokes wavelength. The spatial and intensity behaviour of the Stokes beams are examined as a function of the excitation intensity and Raman gain. Experiments on the image wavelength conversion is conducted with the second harmonics (532 nm) of the Nd:YAG laser and a hydrogen gas as the Raman medium. The images generated at the Stokes wavelength (683 nm) are studied under two parameters, the laser excitation intensity and hydrogen gas pressure. A comparison of the numerical and experimental images is made. It was found that the FD method of solving the SRS wave equations is sufficient to predict the experimental results.
Computer print out.
Keywords: Nonlinear difference equations; Wavelengths; Raman effect